Histone Deacetylase SIRT1 Controls Proliferation, Circadian Rhythm, and Lipid Metabolism during Liver Regeneration in Mice - Bellet, Marina Maria (J Biol Chem, 2016)
Liver regeneration offers a distinctive opportunity to study cell proliferation in vivo. Mammalian silent information regulator 1 (SIRT1), a NAD(+)-dependent histone deacetylase, is an important regulator of various cellular processes, including proliferation, metabolism, and circadian rhythms. In the liver, SIRT1 coordinates the circadian oscillation of clock-controlled genes, including genes that encode enzymes involved in metabolic pathways. We performed partial hepatectomy in WT and liver-specific Sirt1-deficient mice and analyzed the expression of cell cycle regulators in liver samples taken at different times during the regenerative process, by real time PCR, Western blotting analysis, and immunohistochemistry. Lipidomic analysis was performed in the same samples by MS/HPLC. We showed that G(1)/S progression was significantly affected by absence of SIRT1 in the liver, as well as circadian gene expression. This was associated to lipid accumulation due to defective fatty acid beta-oxidation. Our study revealed for the first time the importance of SIRT1 in the regulation of hepatocellular proliferation, circadian rhythms, and lipid metabolism during liver regeneration in mice. These results represent an additional step toward the characterization of SIRT1 function in the liver.